PARE0013 Demystifying Research Jargon: A Volunteer Led Glossary. (9th June 2015) - Taylor, R.; Blackburn, S.; Higginbottom, A.; Rhodes, C.; Dziedzic, K.
Abstract : Background: The terms and acronyms used in research can be confusing to lay people. This volunteer led project aimed to produce a plain language glossary of research terms and acronyms to assist the involvement of Research User Group members in research studies at a primary care research centre. Objectives: To highlight how high quality glossaries for researchers and lay members can be produced by lay volunteers. Methods: A member of the Research User Group (RUG) volunteered to lead the task of compiling a glossary of research terms and acronyms used in research protocols in studies of an Institute of Primary Care. The volunteer generated a list of research terms by a search of study information, discussion with RUG members and study coordinators. With support from the Institute's Patient and Public Involvement team, lay definitions for the research terms were written by the volunteer using a combination of available resources (COCHRANE 1, OMERACT 2, INVOLVE 3 ), web-based searches and creative thinking, and then compiled into a glossary. The glossaries were peer reviewed by Research User Group members and researchers. A glossary of generic research terms and individual study-specific glossaries were created Results: A generic glossary and four study-specific glossaries were produced. The generic glossary contains lay definitions for 332 research terms. The RUG members and researchers described the glossaries as a useful reference to support peoples understanding of the research process. The glossaries are now being widely circulated throughout the Research Institute and externally. The volunteer described the work as a tedious process at times but he has developed new skills and obtained great pride and satisfaction at completing the task. Conclusions: Research glossaries developed by lay volunteers can help Research User Groups better understand and support their contribution to the research process. The glossaries could be translated and made accessible in different formats. As well as sharing their experiences of a particular life experience, volunteers have many other skills and capabilities that can be harnessed to the benefit to the individual and the research team. References: The Cochrane Collaboration. Glossary of Cochrane terms. http://www.cochrane.org/glossary OMERACT Patient Research Partners Group. OMERACT glossary for patient research partners. 2012. http://www.omeract.org/pdf/OMERACT11%20Glossary.pdf INVOLVE. Jargon Buster. http://www.invo.org.uk/resource-centre/useful-information/jargon-buster/ Acknowledgements: We like to convey our gratitude to the Institute's RUG members for their support and help to develop the research glossaries Disclosure of Interest: None declared